Serious Illness and End‐of‐Life Treatments for Nurses Compared with the General Population. Issue 8 (9th July 2019) - Bynum, Julie; Passow, Honor; Austin, Andrea; Carmichael, Donald; Grodstein, Francine
Abstract : OBJECTIVES: As key team members caring for people with advanced illness, nurses teach patients and families about managing their illnesses and help them to understand their options. Our objective was to determine if nurses' personal healthcare experience with serious illness and end‐of‐life (EOL) care differs from the general population as was shown for physicians. DESIGN: Observational propensity‐matched cohort study. SETTING: Fee‐for‐service Medicare. PARTICIPANTS: Nurses' Health Study (NHS) and a random 20% national sample of Medicare beneficiaries aged 66 years or older with Alzheimer's disease and related dementias (ADRD) or congestive heart failure (CHF) diagnosed in the hospital. MEASUREMENTS: Characteristics of care during the first year after diagnosis and the last 6 months of life (EOL). RESULTS: Among 57 660 NHS participants, 7380 had ADRD and 5375 had CHF; 3227 ADRD patients and 2899 CHF patients subsequently died. Care patterns in the first year were similar for NHS participants and the matched national sample: hospitalization rates, emergency visits, and preventable hospitalizations were no different in either disease. Ambulatory visits were slightly higher for NHS participants than the national sample with ADRD (13.1 vs 12.5 visits; P < .01) and with CHF (13.7 vs 12.5; P < .001). Decedents in the NHS and national sample had similar acute care use (hospitalization and emergency visits) in both diseases, but those with ADRD were less likely to use life‐prolonging treatments such as mechanical ventilation (10.9% vs 13.5%; P = .001), less likely to die in a hospital with a stay in the intensive care unit (10.4% vs 12.1%; P = .03), and more likely to use hospice (58.9% vs 54.8%; P < .001). CHF at the EOL results were similar. CONCLUSIONS: Nurses with newly identified serious illness experience similar care as the general Medicare population. However, at EOL, nurses are more likely to choose less aggressive treatments than the patients for whom they care. J Am Geriatr Soc 67:1582–1589, 2019 Abstract : See related editorial by Matlock and Fischer .